Manejemen Pengembangan Sumber Daya Sistem Informasi di SMP Plus Al-Aitam Kabupaten Bandung - Deti Rostini; Wiwik Dyah Aryani; Toha Konidin; Uus Sopandi; Muhammad Ubaydillah; Hasbullah Lau (Departement of Mathematics Education, 2023)
This research uses a qualitative approach with case studies. The data sources used are primary and secondary. As a result of the Planning research, SMP Plus Al-Aitaam has carried out a planning process in the development of information system resources by determining the needs of developing a system including preparing computer hardware, software, databases, procedures, and officers. The planning for the development of information system resources at Al-Aitam Plus Junior High School was drawn up at the beginning of the school year involving the principal, teachers, treasurer and committee. Planning sources of financing for system development by allocating activity funds through the School Activity Plan and Budget (RKAS). Organizing the development of information system resources at SMP Plus Al-Aitaam is carried out by forming a school development team (TPS) that has the responsibility of developing information system resources in schools. The selection of TPS is selected based on the ability to master ICT. The implementation of the development of information system resources at SMP Plus Al-Aitaam is only carried out by providing understanding and motivating the use of existing system resources and not creating new systems due to limited funds and human resources. Supervision and Evaluation is carried out by the principal and the school development team (TPS) either directly or through a written report. Evaluation and monitoring are carried out using various methods, ranging from forming an evaluation team, in person, teacher board meetings, meetings of all school residents or coordination meetings.